Media advocacy and social change: the Case of sexual harassment in Egypt - Hanna, Naglaa Atef Beshay (AUC Knowledge Fountain, 2015)
Social Change and media advocacy are two related concepts. In Egypt with all the changes that are taking place on the political level, social change is needed in parallel to achieve development. Sexual harassment is an alarming phenomenon that is growing in Egypt in the last few years. Media advocacy is a tool that should be included in the strategy to combat this phenomenon as it contributes to make social change which could eliminate the phenomenon. This study reviews some of the media advocacy attempts in Egypt that targets sexual harassment. It also studies the role of the governmental organizations as well as the civil society organizations in using media advocacy for combating sexual harassment and presents recommendations to maximize their benefits from using media advocacy to solve social problems in Egypt like Sexual Harassment.